Preparation of mxene-derived vanadium pentoxide NiFe2O4/V2O5 composites for visible light photodegradation of dyestuff and antimicrobial activity - Choong, Man Kit (2021)

(untitled)
Industrial dyestuff wastewater contained various toxic organic and pathogenic microorganisms which can cause severe environmental pollution if the wastewater is directly discharged into natural water bodies. Heterogeneous semconductor photocatalysis is a green and effective which can use sunlight energy to treat the numerous refractory substrates including the dyestuff wastewater and harmful mcrobes. In the present study, the delaminated-MXene/Nickel Ferrite/Vanadium Pentoxide (D-M/NFO/V) ternary composite was synthesized through a simple thermal decomposition method and employed in the photodegradation of Rhodamine B (RhB) under LED light irradiation. The as-synthesized hotocatalysts were characterized through FESEM, EDX, XRD, UV-vis DRS and Potentiostat. Ternary D-M/NFO/V compound demonstrated reduction in band gap energy with effective charge carrier separation. Using RhB as a targeted pollutant, the ternary D-M/NFO/V composite exhibited the best photocatalytic performance (88.7%) than those of binary Nickel Ferrite/Vanadium Pentoxide (NFO/V) and unary photocatalysts over 4 h of irradiation. The enhanced photocatalytic performance was attributed to its unique morphology, smaller band gap and excellent photoelectrochemical properties. The effect of process parameters including the NFO loadings in binary NFO/V composite, D-M co-catalyst loadings in D-M/NFO/V ternary compound and solution pH were investigated. The results demonstrated that the optimized NFO loadings were 50 wt%, D-M loadings were 0.5 wt% and operated at pH 12. Besides, the antimicrobial activity of the as viii synthesized photocatalysts was evaluated on the microbial inactivation towards Staphylococcus aureus (S. aureus) and Bacillus cereus (B. cereus). Among the photocatalysts, the ternary D-M/NFO/V composite showed the highest microbial inactivation performance over the period of 4 h. Moreover, the dominant species in treating dyestuff was determined through the radical scavenging experiment and both superoxide anions (•O2-) and hydroxyl (•OH) radicals were the major reactive oxygen species (ROS) which were responsible for the photocatalysis in this study. Furthermore, the D-M/NFO/V ternary compound also displayed outstanding recyclability which attained high removal efficiency of 84.2% after four successive runs. Lastly, the optimized ternary composite was successfully tested using real printed ink wastewater to reveal its potential application in the wastewater purification